A new species of the genus Astragalus (Leguminosae) from Northwest Iran - Bidarlord, Mahmoud; Ghahremaninejad, Farrokh; Maassoumi, Ali Asghar (Phytotaxa, 2016)
A new species Astragalus taleshensis (Astragaleae; Leguminosae) is described and illustrated here as a new species from the Talesh Mountains in northwestern Iran. This species belongs to section Malacothrix. Diagnostic morphological characters in discriminating this new species from its close relative A. khajiboulaghensis are tabulated. Some notes are presented on the ecology, distribution, and conservation status of the new taxon. Also, some other species belong to section Malacothrix that occur in the Talesh Mountains are listed.